2019
DOI: 10.1002/jrs.5676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heteroatom doping on the hydrogenation of volleyballene

Abstract: In this study, the heteroatom doping of volleyballene with N and P atoms and the hydrogenation of their related structures is addressed, with an emphasis on the displayed bonding, adsorption energies, and vibrational properties. It is determined that the doping with 12 phosphorus atoms ([Sc20C48P12]‐1] produces a tetrahedral‐like (T point group) structure. Conversely, the presence of 12 nitrogen atoms results in a structure (C2H‐Sc20C48N12) maintaining the parent volleyballene framework. The N‐doping structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This behavior could be attributed to the presence of P and N atoms that are known to have lone pairs and to produce strong structural changes in the pristine volleyballene. 11 Regarding the capacity of P-doped structures to interact with NO molecules, we tested one (Figure 1B), two (Figure 1C), and four molecules (Figure 1D), respectively. In terms of energy, initially one NO molecule is located inside the P-doped structure (resulting in [(N + O)@Sc 20 C 48 P 12 ] À1 ), and the formation of one P-P bond (2.21 Å) reduced the energy of the structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior could be attributed to the presence of P and N atoms that are known to have lone pairs and to produce strong structural changes in the pristine volleyballene. 11 Regarding the capacity of P-doped structures to interact with NO molecules, we tested one (Figure 1B), two (Figure 1C), and four molecules (Figure 1D), respectively. In terms of energy, initially one NO molecule is located inside the P-doped structure (resulting in [(N + O)@Sc 20 C 48 P 12 ] À1 ), and the formation of one P-P bond (2.21 Å) reduced the energy of the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Despite NO molecule in pristine volleyballene, preferred the outside part of it, in P ‐ and N ‐doped volleyballenes, the preference changed toward the inner part (more than 0.5 eV). This behavior could be attributed to the presence of P and N atoms that are known to have lone pairs and to produce strong structural changes in the pristine volleyballene 11 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results revealed that after modification, ZnO nanoplatelets became smaller and embedded in the materials used for the modification. Salas‐Zepeda and Tiahuize‐Flores [ 91 ] used Raman and IR to study the effect of nitrogen and phosphorous doping on the hydrogenation of volleyballene. Their assignment of the IR/Raman bands was carried out to facilitate the experimental detection of these N‐ and P‐doped species.…”
Section: Nanomaterialsmentioning
confidence: 99%